Fulmarus glacialis (Procellariidae) - Landung am Brutfelsen - Rüppell, Georg (IWF (Göttingen), 1970)
Eissturmvogel. Das "Wedeln" ist eine Flugtechnik, die beim Bremsen, Steuern und bei der Erzeugung von Auftrieb angewandt wird. Mit Zeitdehnung. : The first shot shows the cliff face which houses the breeding colony. This is followed by an approach sequence, shot at a speed of 24 f/s. Seven approaches and five landings, shot at 48 f/s, permit the analysis of braking and steering manoeuvres.